-8(4+9x)=7(-2-11x) First start by multiplying each number outside the parentheses by the number and coefficients inside the parentheses

(-8 X 4) + (-8 X 9x) = (7 X -2) - (7 X 11x) The reason the 11x is not -11x is because the solution is already being subtracted.

(-32) + (-72x) = (-14) - (77x)

32 + (-32) + (-72x) = (-14) - (77x) +32 Now add 32 to each side which will make the 32 on the left cancel out.

-72x = 18 - 77x Now add 77x on both sides which will cancel out the -77x on the right side.

-72x + 77x = 18 - 77x +77x

5x = 18 Divide 5 on both sides

5x/5 = 18/5

x = 3.6 The Answer!

-8(4+9x)=7(-2-11x)

-32-72x=-14-77x

-32-72x+72x=-14-77x+72x

-32=-14-5x

-32+14=-14-5x+14

-18=-5x

-18/-5=-5x/-5

x=3.6

First, we'll move the brackets from the right side, to the left side. For this reason, we'll subtract the product 7(-2-11x) both sides:

-8(4+9x) - 7(-2-11x) = 7(-2-11x) - 7(-2-11x)

We'll eliminate like terms from the right side:

-8(4+9x) - 7(-2-11x) = 0

Now, we'll remove the brackets:

-32 - 72x + 14 + 77x = 0

We'll combine like terms:

5x - 18 = 0

We'll isolate x to the left side. For this reason, we'll add 18 both sides:

5x - 18 + 18 = 18

We'll eliminate like terms:

5x = 18

We'll divide by 15 both sides:

x = 18/5

x = 3.6

**The solution of the equation is x = 3.6.**

To determine x using the equation -8(4+9x)=7(-2-11x)

open the brackets,

=>-8*4-8*9x=-2*7-7*11x

=>-32-72x=-14-77x

bring the terms with x to one side and take the numbers to the other

=>-72x+77x=-14+32

=>5x=18

divide both the sides by 5

=>x=18/5

**Therefore x=18/5.**

-8(4+9x) = 7(-2-11x).

To solve this open yhe brackets both sides;

-8*4 +-8*9x = 7*-2 +7*-11x

-32-72x = -14-77x .

Add 77x:

-32-72x+77x = -14.

Add 32:

5x = -14+32

5x = 18

Divide by 5:

x = 18/5 = 3.6

x = 3.6